Laser Irradiation Alters the Expression Profile of Genes Involved in the Extracellular Matrix In Vitro - Sandra M. Ayuk; Nicolette N. Houreld; Heidi Abrahamse (International Journal of Photoenergy)
The extracellular matrix (ECM) forms the basis of every phase in wound healing. Healing may be impaired if some of these components are destroyed. Photobiostimulation has demonstrated a stimulatory response in biological processes. This study aimed to evaluate various genes involved in the ECM, in response to laser irradiation. Isolated human skin fibroblasts were used in three different cell models, namely, normal, normal wounded, and diabetic wounded. Cells were irradiated with 5 J/cm2 using a continuous wave diode laser emitting at a wavelength of 660 nm and incubated for 48 h. Nonirradiated (0 J/cm2) normal and diabetic wounded cells served as the control. Real-time reverse transcription (RT) quantitative polymerase chain reaction (qPCR) was used to determine the expression of 84 genes in a PCR array. There was a significant upregulation of 29 genes in the normal cells, 32 genes in the normal wounded cells, and 18 genes in the diabetic wounded cells as well as a downregulation of 19 genes (normal), 6 genes (normal wounded), and 31 genes (diabetic wounded). Low intensity laser irradiation (LILI) stimulates gene expression in various cell adhesion molecules (CAMs) and extracellular proteins at 660 nm in wounded fibroblasts in vitro.